Exploring perceptual differences and constraints in esports among American university students - Luo, Xianhua; Chen, Li; Chang, Juan; Yang, Yong; Lee, Seoyeon (Frontiers in Sports and Active Living, 2025)
Esports have become a popular competitive gaming and intramural activity in higher education institutions. This study explores perceptual differences and constraints in Esports among American university students. 590 university students completed the Profile of Esports Perception—pre-validated questionnaire of five perceptual factors, namely attraction, economics, recognition, socialisation, and technicity. Multivariate analysis of variance and analysis of variance were utilised to assess the significant perceptual differences in Esports. Results revealed that recognition and socialisation were the lowest and highest scoring factors among the five perceptual factors, respectively. Findings indicated significant differences between male and female students, as well as sports players and non-players across attraction, economics, socialisation, recognition, and technicity. Significant differences were also observed in subgroups gender, playing status, and years played with respect to the negative factor of constraints. The findings may prove valuable to administrators of higher education institutions in understanding the opportunities and challenges of Esports.